BENEFITS AND DANGERS OF USING CHATGPT (Information systems and technologies security, 2024)
Background. This article presents ChatGPT - a new chatbot, one of the latest products in the field of artificial intelligence, created by OpenAI, which developed this technology together with Elon Musk. The article provides recommendations for connecting to a chatbot. The main advantages of artificial intelligence are defined, and examples of its application are given. Current educational processes should develop a cross-disciplinary and practice-oriented approach in the student.Results. It is shown that among the main advantages of ChatGPT is the ability to generate texts on a given topic, to answer almost all user questions, and to express oneself even in Ukrainian. Specific examples of chatbot questions related, in particular, to information protection, risk management, etc., are given. Demonstrated responses from his side. Focused on the dangers of using a new chatbot. It is shown that possible plagiarism, compatibility issues, malicious use, privacy issues, copyright infringement issues, and problems of using ChatGPT in the educational system occupy a special place among the identified dangers. It is emphasized that the education system is currently experiencing a significant crisis and that the process of obtaining knowledge is adequate to the challenges of today, it is necessary to radically revise the approach to what the current teacher and the educational process itself should be. It is noted that Ukraine needs a fundamental transformation of the very essence of the education system. Now the main task of the teacher is to give the student himself the opportunity to take the initiative in learning, to effectively use the information received, to combine it and to apply the received result in solving his task. A successful student must learn to solve complex tasks that are at the junction of various subjects and disciplines. Conclusions. So, ChatGPT is a powerful tool, but today it has some drawbacks that should be considered if you plan to use it.
Keywords: chatbot; neural networks; application; encryption; copyright; privacy; artificial intelligence